2017
DOI: 10.1111/jep.12795
|View full text |Cite
|
Sign up to set email alerts
|

Smallest detectable change and test‐retest reliability of a self‐reported outcome measure: Results of the Center for Epidemiologic Studies Depression Scale, General Self‐Efficacy Scale, and 12‐item General Health Questionnaire

Abstract: To confirm that the change was not a result of measurement error, a score of self-reported outcome measurement scales would need to change by an amount greater than these SDC values. This has important implications for clinicians and epidemiologists when assessing outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 53 publications
0
23
2
Order By: Relevance
“…Our pre‐post effect size of 0.94 (large effect) for the CES‐D was larger than the pre‐post effect size of 0.51 (medium effect) reported in a previous study (Walsh, Eisenlohr‐Moul, & Baer, 2016) that employed a 4‐week mindfulness‐based intervention. In addition, the results of this study considerably exceed the measurement error of CES‐D (Ohno et al, ). It has been shown that unconsciously presented information can affect behaviour (Aoyama et al, ; Van den Bussche et al, ).…”
Section: Discussioncontrasting
confidence: 49%
“…Our pre‐post effect size of 0.94 (large effect) for the CES‐D was larger than the pre‐post effect size of 0.51 (medium effect) reported in a previous study (Walsh, Eisenlohr‐Moul, & Baer, 2016) that employed a 4‐week mindfulness‐based intervention. In addition, the results of this study considerably exceed the measurement error of CES‐D (Ohno et al, ). It has been shown that unconsciously presented information can affect behaviour (Aoyama et al, ; Van den Bussche et al, ).…”
Section: Discussioncontrasting
confidence: 49%
“…40 Any changes smaller than the SDC to the ASAS HI summary score are likely to be due to measurement error and only changes larger than SDC should be considered as real changes. 41 According to the COSMIN guidelines, a sample size of ≥100 indicates excellent quality of evidence for structural validity. 42 As suggested by the protocol, only 25% of patients recruited in the validity component will be followed up longitudinally for the test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…SEM was calculated using the formula SEM = standard deviation of the mean ASAS HI score change × (square root of [1 – ICC]) . Any changes smaller than the SDC to the ASAS HI summary score are likely to be due to measurement error and only changes larger than SDC should be considered as real changes …”
Section: Methodsmentioning
confidence: 99%
“…A score of 16 or higher indicates the possibility of depression. The CES-D is one of the most widely applied indicators of PSD( Meader et al, 2014 ), and its reliability and validity have been documented ( Ohno et al, 2017 ; Shima et al, 1994 ; Shima et al, 1985 ; Meader et al, 2014 ; Towfighi et al, 2017 ; Shinar et al, 1986 ).…”
Section: Methodsmentioning
confidence: 99%